(untitled) (American Journal of Energy and Natural Resources, 2025)
With the global reliance on toxic and environmentally harmful batteries, communities are actively seeking sustainable materials to lessen the reliance on finite resources to foster a circular economy. This paper aimed to create a sustainable and cost-efficient alternative energy source by harnessing mechanical energy from bodily movements. The tilapia fish scales underwent a demineralization process using different solvents (EDTA, Acetic Acid, and Hydrochloric Acid) to enhance their piezoelectric properties and were dried under reduced pressure. Three prototypes were fabricated, each demineralized with different chemical solutions. These prototypes were tested for their voltage output under different mechanical applications such as finger pressing, hand slapping and foot pressing. The highest-performing prototype, treated with 0.05M hydrochloric acid, produced a maximum open-circuit voltage of approximately 39V, demonstrating the effectiveness of the Bio-PENG in generating electricity from ambient mechanical energy. Findings suggest that tilapia fish scales Bio-PENG can serve as a sustainable, flexible, and portable power solution, particularly for regions with limited access to electricity.